INTEGRASI TEKNOLOGI DIGITAL SENSOR DAN MEKANIK PADA FASAD BANGUNAN PERKANTORAN - Wiraguna, Sidi Ahyar; Purwanto, L.M.F (Journal of Architectural Design and Development (JAD), 2024)
In an era of climate change and demands for environmental sustainability, office building facades face the challenge of responding efficiently to changing weather conditions. This research aims to integrate digital and mechanical sensor technologies in facades to create responsive systems, increase energy efficiency, and improve occupant comfort. Using a mixed methodology involving literature analysis, case studies, and computational simulations, this research explores the potential of dynamic facades in responding to environmental variables such as temperature, lighting, humidity, and noise. The results show that the integration of sensor and mechanical technologies enables the facade to dynamically adjust to external conditions, reduce the energy load on the building, and improve thermal and visual comfort for occupants. Furthermore, this research identifies design strategies that can be applied in the development of responsive office building facades, focusing not only on aesthetic aspects, but also on the function of adaptation and interaction with the environment. The conclusion of this research shows that the use of sensor and mechanical technologies in building facades is a significant step forward in digital architecture, with great potential to increase energy efficiency and improve the quality of life in office environments. This research makes an important contribution to the literature in the fields of digital architecture and sustainable development, offering new insights into responsive and adaptive building façade design. The implications of the findings point to new directions for the development of building facades that are more interactive and responsive to their surroundings.